Consistent expression of guanylyl cyclase-C in primary and metastatic gastrointestinal cancers. - Hadi Danaee (PLoS ONE, 2017)
The transmembrane receptor guanylate cyclase-C (GCC) has been found to be expressed in colorectal cancers. However, limited data are available on GCC protein expression in non-colorectal gastrointestinal tumors and few studies have reported whether GCC protein expression was consistently preserved in synchronous primary and metastatic cancer tissues.GCC protein status was assessed by immunohistochemistry in tumor specimens from individuals (n = 627) with gastrointestinal tumors, including esophageal (n = 130), gastric (n = 276), pancreatic (n = 136), and colorectal (n = 85) primary and metastatic tumors. Tissue specimens consisted of tissue microarrays containing esophageal, gastric, pancreatic tumors, and whole-slide tissue sections from colorectal cancer patients with matching primary and metastatic tumors.Among the evaluated esophageal, gastric, and pancreatic tumors, the frequency of GCC positivity at the protein level ranged from 59% to 68%. GCC was consistently expressed in primary and matched/synchronous metastatic lesions of colorectal cancer tissues derived from the same patients.This observational study demonstrated the protein expression of GCC across various gastrointestinal malignancies. In all cancer histotypes, GCC protein localization was observed predominantly in the cytoplasm compared to the membrane region of tumor cells. Consistent immunohistochemistry detection of GCC protein expression in primary colorectal cancers and in their matched liver metastases suggests that the expression of GCC is maintained throughout the process of tumor progression and formation of metastatic disease.